Prevalence of Carbapenem Resistance and their Genotypic Profile among Gram-Negative Bacteria in a Tertiary Care Hospital in Western India - Das, Parijat; Shrutiraaj, Kumar Anand; Ranjan, Manish; Sen, Sourav (Annals of Pathology and Laboratory Medicine, 2021)
Background: Resistance to carbapenems due to carbapenemases has been increasingly noticed worldwide. Detection of carbapenemases among Gram‑negative bacteria (GNB) is important for both clinicians and infection control practitioners. Both phenotypic and molecular methods can be used for detection of Carbapenemases production. Molecular methods although the gold standard for detection of carbapenemases are not used routinely as they might not be immediately available coupled with expertise required, cost and infrastructure incurred and limited by the number of targets detected. Methods: Consecutive non-repeat gram negative isolates isolated from various clinical specimens from intensive care unit (ICU) were included in the study. Antimicrobial susceptibility testing was done on Mueller Hinton’s agar by Kirby Bauer Disc diffusion method as per the Clinical and Laboratory Standards Institute (CLSI) guidelines. Isolates resistant to Meropenem were further screened for carbapenemase producing genes using multiplex polymerase chain reaction (PCR). The results were statistically analysed. Result: A total of 350 gram negative bacteria were screened for carbapenem resistance. Carbapenem resistance was found in 109 GNB. The metallo‑ β‑lactamases were most common carbapenemases followed by KPC. Conclusion: Carbapenemase producing bacteria are a major threat of the 21st century. Preventing emergence and spread of these pathogens through strict infection control practices, judicious use of antibiotics and early and timely detection will contribute in preserving carbapenems, the last resort antibiotics.